tPA Helpers in the Treatment of Acute Ischemic Stroke: Are They Ready for Clinical Use? - Kim, Jong S. (J Stroke, 2019)
Tissue plasminogen activator (tPA) is the only therapeutic agent approved to treat patients with acute ischemic stroke. The clinical benefits of tPA manifest when the agent is administered within 4.5 hours of stroke onset. However, tPA administration, especially delayed administration, is associated with increased intracranial hemorrhage (ICH), hemorrhagic transformation (HT), and mortality. In the ischemic brain, vascular remodeling factors are upregulated and microvascular structures are destabilized. These factors disrupt the blood brain barrier (BBB). Delayed recanalization of the vessels in the presence of relatively matured infarction appears to damage the BBB, resulting in HT or ICH, also known as reperfusion injury. Moreover, tPA itself activates matrix metalloproteases, further aggravating BBB disruption. Therefore, attenuation of edema, HT, or ICH after tPA treatment is an important therapeutic strategy that may enable clinicians to extend therapeutic time and increase the probability of excellent outcomes. Recently, numerous agents with various mechanisms have been developed to interfere with various steps of ischemia/ reperfusion injuries or BBB destabilization. These agents successfully reduce infarct volume and decrease the incidence of ICH and HT after delayed tPA treatment in various animal stroke models. However, only some have entered into clinical trials; the results have been intriguing yet unsatisfactory. In this narrative review, I describe such drugs and discuss the problems and future directions. These “tPA helpers” may be clinically used in the future to increase the efficacy of tPA in patients with acute ischemic stroke.